MicroRNA-31 inhibits traumatic brain injury-triggered neuronal cell apoptosis by regulating hypoxia-inducible factor-1A/vascular endothelial growth factor A axis. Issue 1 (1st December 2021) - Qian, Yan; Li, Xin; Fan, Raofei; Li, Qiaofen; Zhang, Yang; He, Xiaona; Yang, Wei; Sun, Wei; Lv, Shaokun
Abstract : MicroRNAs are dysregulated in traumatic brain injury and are involved in neuronal cell behaviors. Previous studies identified miR-31 as a spinal cord injury-related microRNA, while its role in traumatic brain injury remains indistinct. Herein, we explored the participation of miR-31 in traumatic brain injury. Traumatic brain injury model was established after traumatic neuron injury. Neurocytes were transfected with miR-31 mimic or inhibitor. Cell counting kit-8, lactate dehydrogenase assay, terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling, and western blot were applied to examine cell viability, lactate dehydrogenase releasing, apoptosis, and apoptosis-related protein. The binding between miR-31 and hypoxia-inducible factor-1A was verified by luciferase assay. Quantitative reverse transcription-PCR was used to detect the regulation of traumatic neuron injury or hypoxia-inducible factor-1A overexpression on vascular endothelial growth factor A level. The effects of hypoxia-inducible factor-1A or vascular endothelial growth factor A on neuronal cell injury were examined. Additionally, phosphatidylinositol 3kinase/AKT/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway was also examined using western blot. Downregulation of miR-31 promoted traumatic neuron injury-induced neuronal cell injury, and its overexpression did the opposite. Hypoxia-inducible factor-1A acted as a downstream mRNA of miR-31 and its downregulation was involved in miR-31-regulated neuronal cell injury. Vascular endothelial growth factor A level was elevated by traumatic neuron injury or hypoxia-inducible factor-1A overexpression. Hypoxia-inducible factor-1A enhanced neuronal cell injury via promoting vascular endothelial growth factor A expression. Furthermore, miR-31/hypoxia-inducible factor-1A/vascular endothelial growth factor A regulated PI3K/AKT/mTOR pathway in neuronal cells. Our study demonstrated miR-31 inhibited neuronal cell apoptosis via regulating hypoxia-inducible factor-1A/vascular endothelial growth factor A axis.